Development and validation of selective UV spectrophotometric analytical method for budesonide pure sample - Shakuntala, Pushp Bharti, Neetu Sachan, Phool Chandra, Kavita GahloMallikarjuna Gouda M, Ramakrishna Shabaraya. A, Shantakumar S.M, Somashekar Shyale. S, Putta Rajesh kumar (Journal of Applied Pharmaceutical Science)
Budesonide is a very potent corticosteroid, used for bronchial asthma and inflammatory bowel disease. Objective of the present investigation is to develop the simple and selective UV spectrophotometric method for quantification of budesonide in bulk sample. Absorption maximum of budesonide was found to be 246.0 nm and obeyed the beers law in the concentration range of 1.4 to 25 µ g/ml. Calibration curve shows a linear relationship between the absorbance and concentration in the range of 2 to 10 µ g/ml and the limit of detection is 0.01 µ g/ml. The limit of quantification was found to be 1.4 µg/ml. The method was validated for repeatability, accuracy and precision. The percent amount of recovery was 99 - 100% with minimum standard deviation less than 1%. Obtained results showed there is minimum intra day and inter day variation. The excipients present in the preparation did not interfered during the analysis. Developed analytical UV spectrophotometric method is simple, rapid and reproducible and further it can be used for estimation of drug in bulk and colon matrix tablet dosage form.
Keywords: Budesonide, UV method development, Validation studies